Design risk management : contribution to health and safety - Summerhayes, Stuart. (Blackwell, 2010)
The Construction (Design and Management) Regulations 2007 (CDM Regulations 2007) is a revision of a major piece of legislation within the wide portfolio of construction-related legislation. It seeks to improve the long term health and safety performance of the UK construction industry, with ownership of health and safety proactively undertaken by the integrated project team. € Good design has always embraced health and safety issues and design teams remain essential players as well as key contributors and communicators in matters of health and safety management. De signers have a legal responsibility to ensure that their designs account for health and safety at all stages within the holistic envelope of construction. Design Risk Management: Contribution to Health and Safety gives detailed guidance to construction practitioners with design responsibility on how to identify and manage health and safety risks, and on the design strategies to be followed. It seeks to focus on accountability with due emphasis on the minimisation of unnecessary bureaucracy and offers documentation trails that provide an insight to managing risk and not paperwork. Subsequently it offers a process by which designers can discharge their duties in compliance with the CDM Regulations.